COUNTER DIGITAL SYSTEM USING MICRO CONTROLLER (MCS) -8031 - Shougi Shabal; Ir. Irwan Nirmara. MM Ir. Irwan Nirmara. MM (Jurnal Sistem Komputer, 2000)
Microcontroller-8031 is a minimum system that can combine the input and output adigital signal that can be used for the control of an application tool, primarily locatedin industrial. By using an 8031 microcontroller-system device can be controlledsimultaneously / together as well as reliable, because the microcontroller-8031 has aprivilege in terms of hardware.With its features, the microcontroller-8031 can be very useful for the development oftechnology, especially in digital control systems are very efficient and effective.Microcontroller system is a control center of the overall work system.Microcontroller for digital circuits are used as a store counter or control commandsfrom the calculations that will be shown at 7-segment display.Among the advantages to use microcontroller-8031 in this series is due to thepresence of all devices are required, so no longer need a computer and interface, sono longer need a computer and an interface so that the circuit becomes moreeconomical and efficient. whereas in data processing within the systemmicrocontroller, 8031 assembly language is used.